R&D Investments and Corporate Cash Holdings - Guido Baldi; André Bodmer (Economics of Innovation and New Technology, 2018)
This paper presents evidence about how research and development (R&D) expenditures affect corporate cash holdings in European country groups that differ in their innovation capacity. In theory, one can expect intangible investments such as R&D to result in higher cash stocks than fixed investments, particularly because intangible capital is less suitable as collateral for obtaining external funds. The relationship can be expected to be particularly strong in innovative countries. These countries carry out a relatively high proportion of cutting-edge R&D, which tends to be particularly risky and may be associated with substantial gestation lags before becoming productive. These features tend to increase firms' precautionary cash holdings. To investigate this issue in a European context, we examine different groups of countries that are clustered based on differences in their innovative capacity. Our estimation results confirm a positive relation between changes in R&D investment and changes in cash holdings, whereas changes in fixed investment do not appear to be related to changes in cash positions. The impact of changes in R&D on cash tends to be higher for country groups characterized by a high level of innovative capacity than for countries with moderate levels of innovative capacity. However, the differences across country groups are less pronounced than expected.
Keywords: G31; G32; O16; 330; cash holdings; intangible investment